2017
DOI: 10.1093/nar/gkw1306
|View full text |Cite
|
Sign up to set email alerts
|

FEELnc: a tool for long non-coding RNA annotation and its application to the dog transcriptome

Abstract: Whole transcriptome sequencing (RNA-seq) has become a standard for cataloguing and monitoring RNA populations. One of the main bottlenecks, however, is to correctly identify the different classes of RNAs among the plethora of reconstructed transcripts, particularly those that will be translated (mRNAs) from the class of long non-coding RNAs (lncRNAs). Here, we present FEELnc (FlExible Extraction of LncRNAs), an alignment-free program that accurately annotates lncRNAs based on a Random Forest model trained with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
397
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 318 publications
(421 citation statements)
references
References 71 publications
2
397
0
Order By: Relevance
“…Mikado transcriptome discussed above was filtered for known protein-coding genes. The remaining transcripts were the basis for identification of lncRNAs using FEELnc pipeline (Wucher et al 2017). In total 5,874 lncRNA genes were predicted with 6,694 alternately spliced isoforms.…”
Section: Long Non-coding Rna Identificationmentioning
confidence: 99%
“…Mikado transcriptome discussed above was filtered for known protein-coding genes. The remaining transcripts were the basis for identification of lncRNAs using FEELnc pipeline (Wucher et al 2017). In total 5,874 lncRNA genes were predicted with 6,694 alternately spliced isoforms.…”
Section: Long Non-coding Rna Identificationmentioning
confidence: 99%
“…Accumulating evidence showed that the protein-coding genes are accounted for only 50% of inal assembled transcriptome data. Mining inal non-redundant transcriptome data via long non-coding RNA identiication tools such as PLEK [90], lncRScan-SVM [91], FEELnc [92] or measuring protein coding potential of transcripts using various tools such as coding potential calculator (CPC) [93], coding potential assessment tool (CPAT) [94], coding-non-coding index (CNCI) [95] provides us more information about the transcriptome landscape of non-model organism.…”
Section: Transcriptomics Tells More: Focusing On Speciic Annotation Tmentioning
confidence: 99%
“…Several methodologies have been described to identify/distinguish lncRNAs from mRNAs and successfully applied to livestock species such as coding potential calculator (CPC) [122], PhyLoCSF [123], coding-non-coding index (CNCI) [124], coding potential assessment tool (CPAT) [125], Predictor of Long non-coding RNAs and mRNAs based on an improved k-mer scheme (PLEK) [126] and Flexible Extraction of LncRNAs (FEELnc) [127], etc. The FEELnc program developed by the functional annotation of animal genome project consortium (FAANG) [128] is recommended as a standardized protocol for lncRNA analyses in animal species.…”
Section: Tools For Lncrna Identiicationmentioning
confidence: 99%
“…The FEELnc program developed by the functional annotation of animal genome project consortium (FAANG) [128] is recommended as a standardized protocol for lncRNA analyses in animal species. In order to distinguish lncRNAs from mRNAs, FEELnc program uses a machine-learning method for estimation of a protein-coding score according to the RNA size, open reading frame coverage and multi k-mer usage [127]. The FEELnc program can derive an automatically computed cut-of so it maximizes the lncRNA prediction sensitivity and speciicity.…”
Section: Tools For Lncrna Identiicationmentioning
confidence: 99%